Estimation of silver nanoparticles effect on the reproductive health of female Wistar rats. Issue 1 (31st December 2022) - Mohamed, Yara; El Ghareeb, Abdel-Wahab; Attaby, Fawzy Ali; Abd El-Rahman, Heba Ali
ABSTRACT: The present study aimed to study the effect of Silver nanoparticles (AgNPs) on the reproductive health of female Wistar rats. Twenty-one adult female rats in the estrus phase were divided into three groups. Seven rats each, Group (I) was the control group, Group (II) received a low dose of 2 mg/kg of AgNPs, and Group (III) received a high dose of 4 mg/kg of AgNPs. Rats were intraperitoneally (I.P.) injected three days per week for 30 days. After 24 hours from the last treatment, the rats were sacrificed under anesthesia. The results indicated no change in body weight or relative and absolute weight of reproductive organs. The biochemical results showed decreased estrogen hormone levels and no change in progesterone hormone levels. High dose group revealed a significant increase in follicle-stimulating and luteinizing hormone. AgNPs caused a significant decrease in total antioxidant capacity and a significant increase in malondialdehyde levels. AgNPs induced ovarian follicles degeneration. The uterine epithelial cells showed a high level of hyperplasia, losing their columnar shape showing apoptosis and inflammation. Immunohistochemistry studies showed a significant increase in activated caspase-3. This study showed the harmful effect of AgNPs on reproductive tissues, which may increase the chance of infertility.